Impact of CGIAR Mega Programs ‘on the ground’ requires development and policy partnerships - Hall, S. (International Livestock Research Institute, 2010)
Steve Hall, Director General of the WorldFish Centre elaborates on the changed roles that CGIAR Centers will have to through the Mega Program approach. The new approach adds a layer of responsibilities and accountability for centers to work more explicitly with development and policy partners, “to really have impact on the ground.” He was speaking in the margins of the CGIAR Livestock Fish Mega Program stakeholder consultation meeting in Addis Ababa, 24 and 25 August 2010.